2016
DOI: 10.1021/acs.orglett.6b02845
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-Controlled Selectivity Switch in the Three-Component Coupling Involving Arynes, Aromatic Tertiary Amines, and CO2

Abstract: The transition-metal-free multicomponent coupling involving arynes, aromatic tertiary amines, and CO is reported. The reaction exhibits switchable selectivity depending on the electronic nature of the aromatic amines used. With amines bearing electron-releasing/neutral groups as the nucleophilic trigger, the reaction afforded 2-arylamino benzoates via a nitrogen to oxygen alkyl group migration. Employing electron-deficient amines in the reaction furnished 2-aminoaryl benzoates proceeding via the aryl to aryl a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(11 citation statements)
references
References 51 publications
0
10
0
1
Order By: Relevance
“…46 Biju and co-workers reported that MCRs of arynes with tertiary aromatic amines and carbon dioxide formed zwitterionic intermediate 33, which could undergo either N→O alkyl or aryl group migration to generate anthranilic acid derivatives (Scheme 12). 47…”
Section: Account Syn Lettmentioning
confidence: 99%
“…46 Biju and co-workers reported that MCRs of arynes with tertiary aromatic amines and carbon dioxide formed zwitterionic intermediate 33, which could undergo either N→O alkyl or aryl group migration to generate anthranilic acid derivatives (Scheme 12). 47…”
Section: Account Syn Lettmentioning
confidence: 99%
“…The Biju group disclosed an amino-carboxylation of arynes using aniline derivatives (Scheme 3). 9 This method offers a divergent approach for the synthesis of differentially substituted acyl-aminated arenes depending on the electronics of the aniline ring.…”
Section: Scheme 2 Aryne Insertion Into Imidesmentioning
confidence: 99%
“…In 2008, Yoshida and co-workers documented a concise three-component coupling of benzynes, secondary amines, and CO 2 , furnishing anthranilic acids directly (Scheme , eq c). Interestingly, with the introduction of aromatic tertiary amines to the reaction, Biju and co-workers developed a novel substrate-controlled switchable MCR involving benzynes and CO 2 , delivering two different types of 2-aminoaryl benzoates selectively (Scheme , eq c). Recently, Jiang and co-workers disclosed a new three-phase four-component coupling reaction involving benzynes.…”
Section: Introductionmentioning
confidence: 99%